Impact of Cannabis Seed Incorporation in Layer Diet on Productive Performance and Egg Quality Traits - Yassine Taaifi; Kamal Belhaj; Farid Mansouri; Youssef Rbah; Najlae Elbouanani; Reda Melhaoui; Abdesamad Ben Moumen; Embarek Azeroual; Hana Serghini-Caid; Ahmed Elamrani (Scientifica)
The production of nonindustrial cannabis is highly developed in the Moroccan Rif region; however, local farmers consider hemp seeds which are rich in omega 3 and tocopherols, only as by-products of cannabis cultivation with low market value. The local ecotype is considered to be a plant with a cannabinoid content of more than 0.4%. So, the objective of this research is to investigate how the incorporation of this local hemp seed affects productive performance and egg quality traits. The experiment is conducted to evaluate the effects of hemp seed (HS) incorporation on hen laying performance and physical egg quality at three levels: 10% (HS-10% group), 20% (HS-20% group), and 30% (HS-30% group). Ninety-six Lohmann Brown classic laying hens were randomly assigned to a control group and three feed treatments. The sampling was taken after the 28-week rearing period (peak egg laying). Throughout the experiment, low-rate HS inclusion (HS-10%) showed no significant differences in egg-laying performance (p > 0.05). However, the high incorporation rates of HS (20% and 30%) negatively affected the egg-laying performance (84–94% and 80–86%, respectively). The albumen quality was also improved by the HS inclusion, where the highest values of the Haugh unit were recorded, ranging between 68.69 and 73.91 for the HS-30% groups. The results also show that HS inclusion and duration influence significantly the yolk color (p < 0.001). The yellow intensity decreases with HS incorporation and aging, from a dark yellow (b∗ = 38.63 for the control group) to a very pale yellow (b∗ = 26.29 for HS 30% group). Based on these findings, we can conclude that the incorporation of nonindustrial Moroccan cannabis seeds (ecotype Beldiya) at low rate in the diet of laying hens does not alter the laying performance or the quality of the egg; therefore, they could be used in poultry feeding as an alternative constituent to partially replace high-cost imported ingredients, such as corn and soybeans.